EVALUATION OF THE EFFICACY OF AN OINTMENT CONTAINING GOOSE FAT, EXTRACT ALOE, AND BETAMETHASONE IN PRECLINICAL STUDIES FOR THE TREATMENT OF ALLERGIC DERMATITIS - Karimova F.R. (Central Asian Journal of Medicine, 2025)
This preclinical study, based on modern scientific principles, assessed the biological safety and regenerative efficacy of a topical ointment composed of goose fat, aloe, and Betamethasone. The experiments were conducted using a full-thickness excision wound model in albino rats. The ointment demonstrated no signs of acute toxicity, with treated animals showing stable clinical behavior and body weight. Application of the formulation led to significant acceleration of wound healing, with complete closure observed by day 14. Comparative analysis indicated superior efficacy of the experimental ointment compared to standard treatments. These findings confirm the high regenerative potential and safety profile of the goose fat-based formulation and support its relevance for further clinical development.